5d+d-6d-2-4d=0

Simple and best practice solution for 5d+d-6d-2-4d=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5d+d-6d-2-4d=0 equation:


Simplifying
5d + d + -6d + -2 + -4d = 0

Reorder the terms:
-2 + 5d + d + -6d + -4d = 0

Combine like terms: 5d + d = 6d
-2 + 6d + -6d + -4d = 0

Combine like terms: 6d + -6d = 0
-2 + 0 + -4d = 0
-2 + -4d = 0

Solving
-2 + -4d = 0

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + -4d = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -4d = 0 + 2
-4d = 0 + 2

Combine like terms: 0 + 2 = 2
-4d = 2

Divide each side by '-4'.
d = -0.5

Simplifying
d = -0.5

See similar equations:

| 6(-2t+9)=150 | | 7(2n-9)=77 | | 3(-10+d)=-42 | | 2(9+5k)=-82 | | 6(-3a-7)=-186 | | 4(5k+2)=248 | | 6(8-4k)=96 | | 2(3+x)=-18 | | 7(3k+2)=-238 | | 525/8+68=x | | 525/8+68 | | 5(-7t-9)=-430 | | 3(10+w)=39 | | 3(-5x+8)=-81 | | 4(5+6a)=92 | | 7(-6b+8)=-154 | | 9y-7=19y+83 | | 2(-8+7k)=-16 | | 4(7+2k)=60 | | 2(9+7t)=-66 | | 6(1-7m)=6 | | 2(10-t)=20 | | 15=-2(21-1) | | -10(x-7)-7(k-2)= | | 7(6t+1)=385 | | 75/8*-7 | | 5(2+3w)=130 | | 4(9+2t)=12 | | 75/8*20=x | | 5(3w+9)=120 | | 3(-5w+4)=-3 | | 5(3a+9)=30 |

Equations solver categories